Aesop’s The Fox and the Grapes: A Socio-Linguistic and Sociological Study of Its English Adaptations - Punitha Andrews; S. S. Thakur (Transcript: An e-Journal of Literary and Cultural Studies)
This paper examines the linguistic and sociocultural evolution of Aesop’s The Fox and the Grapes through four significant English translations spanning the 15th to 20th centuries. Through comparative analysis of adaptations by William Caxton (1484), Samuel Croxall (1722), Thomas James (1848), and V.S. Vernon Jones (1912), the study reveals how translation choices reflect changing social contexts, educational priorities, and literary sensibilities. The analysis demonstrates how each translator’s linguistic and narrative strategies were shaped by factors including literacy rates, pedagogical philosophies, and cultural values of their respective eras. While Caxton’s medieval version emphasizes direct moral instruction, later adaptations show increasing sophistication in storytelling techniques and psychological depth, culminating in Vernon Jones’s nuanced early 20th-century interpretation. The study particularly focuses on the sociolinguistic aspects of translation, examining how vocabulary choices, syntactical structures, and narrative techniques evolved to meet the changing needs of their audiences. Furthermore, it explores the broader sociological implications of these adaptations, considering how they reflect and respond to contemporary social, political, and educational developments. This diachronic examination illuminates not only the fable’s remarkable adaptability but also the complex interplay between translation, social change, and literary evolution across centuries of English literary history.